THREE WORTHINESSES OF THE PRESS RELEASE COMMUNICATION - Wijaya, Bambang Sukma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
Amid the development of an increasingly complex and dynamic media and communication ecosystem, press release communication also faces significant challenges. This article shows three aspects and parameters of worthiness in creating and distributing press release communications for maximum impact. First, Newsworthy --how worthy the information is to be reported, includes proximity, recency, humanity, exclusivity, and shareability. Secondly, Storyworthy is how appropriate the information and events presented in the media release are to be told and made viral. It includes theming, plotting, messaging, characterizing, and dramatizing. Lastly, Brandworthy --how worthy a press release is as a branding strategy. Hence, the press release should be distinguishable, soundable, representable, talkable, and marketable. This article is helpful for public relations and corporate communications practitioners and an essential reference for researchers to study the suitability of content, the impact, and the effectiveness of press release communications. How to cite this article (7th APA Style):Wijaya, B. S. (2022). Three Worthinesses of the Press Release Communication. Journal Communication Spectrum: Capturing New Perspectives in Communication, 12(1), 40-48. https://doi.org/10.36782/jcs.v12i1.2365